2019
DOI: 10.1080/09670262.2019.1597925
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic, alien and lost species: molecular diversity ofUlva sensu latoalong the German coasts of the North and Baltic Seas

Abstract: DNA barcoding analysis, using tufA, revealed considerable differences between the expected and observed species inventory of Ulva sensu lato in the Baltic and North Sea areas of the German state of Schleswig-Holstein. Of 20 observed genetic entities, at least four (U. australis, U. californica, U. gigantea and Umbraulva dangeardii) had been introduced recently, whereas three others (one Ulva sp. and two Blidingia spp.) could not be identified at the species level and could also represent recently introduced sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 47 publications
0
49
0
Order By: Relevance
“…Thus, under unmodified (ambient) conditions, the experiments had the following properties; nitrate < 5 μM, phosphate < 1 μM, temperature at 13-14°C and with bubbling of air, a pCO 2 ≈ 400 ppm and agitation were achieved. The starting seaweed material has been utilized in tank cultivations for some time at Tjärnö Marine Laboratory (58°52′ 36.4″ N 11°6 ′ 42.84″ E) and was previously identified as U. fenestrata (Genebank, accession numbers BankIt2249282 Seq1: MN240309, Seq2: MN240310, Seq3: MN240311), through sequencing of the tufA gene (Steinhagen et al 2019). Experimental samples were taken from each experiment and were frozen, lyophilized, homogenized, and stored at < − 20°C until further analysis.…”
Section: Ulva Fenestrata Cultivationmentioning
confidence: 99%
“…Thus, under unmodified (ambient) conditions, the experiments had the following properties; nitrate < 5 μM, phosphate < 1 μM, temperature at 13-14°C and with bubbling of air, a pCO 2 ≈ 400 ppm and agitation were achieved. The starting seaweed material has been utilized in tank cultivations for some time at Tjärnö Marine Laboratory (58°52′ 36.4″ N 11°6 ′ 42.84″ E) and was previously identified as U. fenestrata (Genebank, accession numbers BankIt2249282 Seq1: MN240309, Seq2: MN240310, Seq3: MN240311), through sequencing of the tufA gene (Steinhagen et al 2019). Experimental samples were taken from each experiment and were frozen, lyophilized, homogenized, and stored at < − 20°C until further analysis.…”
Section: Ulva Fenestrata Cultivationmentioning
confidence: 99%
“…The identification of species within genus Ulva has long been recognized as an extremely challenging task, with these green seaweeds displaying a remarkable level of morphological plasticity (e.g., multiple strains occurring within the same species) and cryptic speciation being commonly recorded [34]. These features commonly impair an accurate taxonomic classification of sampled material and cause undesirable taxonomic confusion.…”
Section: Sampling and Storagementioning
confidence: 99%
“…These features commonly impair an accurate taxonomic classification of sampled material and cause undesirable taxonomic confusion. These issues of taxonomic inaccuracy are particularly relevant when targeting species that may yield valuable natural products [34]. In this way, samples collected in the present study were termed as Ulva species.…”
Section: Sampling and Storagementioning
confidence: 99%
“…The samples were initially identified morphologically and were assessed as a feedstock for hydrothermal liquefaction (Raikova et al, 2020). However, recent studies have identified strong morphological plasticity within Ulva spp., as well as the occurrence of cryptic species within the genus (Steinhagen, Karez, & Weinberger, 2019). Thus, the Ulva samples were molecularly identified in this study after the morphological pre-identification.…”
Section: Species Identificationmentioning
confidence: 99%
“…The powder was extracted using an Invisorb Spin Plant Mini Kit (Stratec, Birkenfeld, Germany) following the manufacturer's protocol. The barcode marker tufA was amplified by polymerase chain reaction (PCR) following the procedure as described (Steinhagen et al, 2019). The obtained amplicons were subsequently sequenced by Eurofins Genomics (Konstanz, Germany).…”
Section: Species Identificationmentioning
confidence: 99%